The forgotten language skill: finding a prominent place for listening in meaningful programming for multilingual learners with learning disabilities - Spies, Tracy Griffin (Frontiers in Education, 2023)
Listening is the primary vehicle through which children learn, is fundamental to all other communication competencies, is a core component of multimodal instruction, and is key to learning language. At the same time, listening comprehension is the least understood language skill and is challenging for teachers in the provision of high quality instruction. For multilingual learners with learning disabilities it also presents certain challenges at the intersection of students' disability and developing language proficiency. This article presents a conceptual analysis of listening comprehension across the perspectives of learning disability and second language acquisition in an effort to link disconnected understandings from the fields to address the intersectional needs of multilingual learners with disabilities. These findings are integrated into a framework of listening comprehension for multilingual learners with learning disabilities highlighting the cognitive and linguistic processes necessary for effective listening. Various examples of how to use the framework to plan multilingual learners with learning disabilities' meaningful access to the general education curriculum are presented including its use in planning students' individualized education plans.